TRADISI JONJONG UMAH MASYARAKAT JAWA DI DESA PARIT KEBUMEN KECAMATAN RUPAT KABUPATEN BENGKALIS - Hidayatun Nisa; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out in Parit Kebumen Village, Rupat District, Bengkalis Regency. The background to this issue is that the Jonjong Umah Tradition is a cultural wealth originating from the Parit Kebumen Village. However, as a newly developed village filled with a majority of displaced people from Central Java, this tradition emerged with the existence of the habits and needs of the local community, so that the Javanese Umah tradition and its relation to the Javanese habits of the Parit Kebumen village need to be interpreted. This thesis aims to analyze the value and meaning of the Jonjong Umah tradition of the Javanese community, and to know the purpose of the Jonjong Umah tradition.This research is a qualitative research with a descriptive approach. The data used are primary and secondary methods. Data collection techniques are carried out by observation, interviews, and documentation methods which all answer the research problems regarding the Jonjong Umah tradition. The research informants are the people of Parit Kebumen Village, consisting of traditional leaders, village officials, people who have done Jonjong Umah, people who have never done Jonjong Umah, Village Community Resilience Institutions , and Jonjong Umah guides.Based on the results of the study, it was found that the implementation of this tradition was flexible, not burdensome and difficult, so that there were some villagers of Parit Kebumen who implemented it and did not implement it. The values contained in the Jonjong Umah tadisi are economic values, the value of helping, and religious values. The purpose of implementing the Jonjong Umah tradition is to help the people of Parit Kebumen Village who want to move houses and strengthen the community's friendship when implementing the Jonjong Umah tradition. Keywords: jonjong umah , mutual cooperation, tradition.